A Giant-Cell Lesion with Cellular Cannibalism in the Mandible: Case Report and Review of Brown Tumors in Hyperparathyroidism. (9th February 2017) - Azzi, Lorenzo; Cimetti, Laura; Annoni, Matteo; Anselmi, Diego; Tettamanti, Lucia; Tagliabue, Angelo
Abstract : A small radiolucent area in the mandible was discovered in a 58-year-old woman with no oral complaints. The patient's history included only hypertension. The lesion was considered as an inflammatory cyst and was enucleated. Three months later, a CT revealed the presence of a cyst-like lesion in the mandible with thin expanded buccal cortical plate, localized erosion, and a polylobate appearance on the lingual aspect of the cortical plate. The histological diagnosis of the lesion was central giant-cell granuloma (CGCG). The lesion was thoroughly enucleated. Nevertheless, another X-ray carried out six months later revealed multiple bilateral osteolytic areas throughout the jaw. In addition, widespread cortical plate erosion was observed, as well as signs of root resorption and periodontal enlargement. There was no sign of neurological involvement, although the nerves appeared to be dislocated. After full blood chemistry analysis and detailed collection of radiographs, the final diagnosis was brown tumors in primary hyperparathyroidism. This case report demonstrates how dental clinicians may be the first-line specialists who identify a complex systemic disease before other clinicians. Finally, it highlights the role of cellular cannibalism in predicting the clinical aggressiveness of brown tumors as well as in other giant-cell lesions.